Therapeutic targets in systemic sclerosis - Denton, Christopher P (BioMed Central|1, 2007)
The precise aetiology of systemic sclerosis (SSc) remains elusive, but significant advances over the past few years have improved our understanding of the underlying pathogenic processes and identified key pathways and mediators that are potential therapeutic targets. The situation is complicated by the clinical heterogeneity of SSc and the differential pathogenesis that underlies the two commonest subsets, namely diffuse and limited cutaneous disease. However, there are common mediators that could be targeted to provide clinical benefit in both types of disease. To date, clinical success with therapies directed against logical profibrotic mediators, such as connective tissue growth factor and transforming growth factor-β, is yet to be reported, although studies are ongoing. More promising clinical results have been obtained with the dual endothelin receptor antagonist bosentan, which has been shown to manage two vascular complications of SSc effectively: pulmonary arterial hypertension and digital ulceration. It remains to be determined whether the identification of additional mediators merely furthers our knowledge of the natural history of SSc or presents targets that can be manipulated to manage SSc patients effectively.